Pengaruh Pemberdayaan, Efikasi Diri Dan Etos Kerja Terhadap Kinerja Pegawai Di Kantor Pelayanan Perbendaharaan Negara Medan I - Jaya Putra Abdurrahman Nasution; Agustian Napitupulu; Popi Ardiansyah; Hannida Fatmi Nasution; Ahmad Syukri Lubis; Safrida Safrida (Journal of Business and Economics Research (JBE), 2023)
The formulation of problem in this research how is influence of empowerment on performance. How is influence of self eficacy on performance. How is influence of work ethos on performance. How is influence of empowerment, self eficacy and work ethos on performance. The purpose of this research is for know influence and analize of empowerment on performance. For know influence and analize of self eficacy on performance. For know influence and analize of work ethos on performance. For know influence and analize of empowerment, self eficacy and work ethos on performance. The sample in this research is 30 employees, with data analysis technique used is descriptive analysis and multiple linear regression analysis. The research result is empowerment variable influence positive and significant on performance. Self eficacy variable influence positive and significant on performance. Work ethos variable influence positive and significant on performance, empowerment, self eficacy and work ethos variable influence positive and significant on performance.